STRATEGI INISIASI EKONOMI KREATIF DALAM PENINGKATAN POTENSI PRODUK UMKM KLEPON ASLI BULANG DI SIDOARJO - Nanda, Aditya Surya; Aristyanto, Erwan (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
The aim of PKM-CSR is to help partners manage and develop their businesses more effectively and efficiently, as well as to increase their competitiveness in the market. The application of technology for partners is very important to increase operational efficiency, expand markets and increase competitiveness. The partner's problem is that klepon cake production still relies on traditional methods, lack of variants in production and marketing, resulting in limitations in reaching a wider market, and the financial sector is still weak. Conventional marketing strategies for klepon MSMEs often lack understanding and utilization of effective digital marketing techniques. Suboptimal financial management, manual financial management and lack of use of financial technology cause inefficiency and lack of transparency in financial recording. The solutions needed by Partners are making more product variants less monotonous, using good production equipment, increasing access to technology, providing training and technical assistance to MSME players to adopt digital technology in production and business operations. Development of digital marketing strategies that can help MSMEs design and implement digital marketing strategies through social media, websites and e-commerce platforms. Implementation of a digital financial system: Introducing financial reporting applications to facilitate more efficient and transparent financial management. Product innovation by developing new variants of klepon cake and attractive packaging to increase the product's appeal in the market.